Pemanfaatan Dana Aspirasi Anggota Dprd Maluku Tengah: Studi Pada Daerah Pemilihan VI Kecamatan Pulau Haruku - Moh. Daud Marasabessy (STIA Abdul Azis Kataloka Ambon, 2022)
This study aims to find out how the use of aspiration funds by members of the Central Maluku DPRD, especially in Dapil VI, to find out the distribution of the aspiration funds and how the aspiration funds are accountable. The data collection techniques used are: 1). Interview Guide 2). In-depth observation 3). Documentation and 4). Library Studies. While the data analysis technique begins by examining all available data from various sources, namely from interviews, observations that have been written in field notes, personal documents, official documents, pictures and photos, From the results of the study it can be concluded that 1). For the process of distributing the budget, the aspiration funds of the DPRD Haruku Sub-district, Central Maluku Regency have indeed been fully distributed and given responsibility to the project implementer and it has been implemented, but there is still a system of nepotism in the sense that it still tends to the family element other than that there is no openness or reporting to local state government. 2). The utilization of the aspiration funds for infrastructure development has been right on target, but there is still an element of nepotism in the utilization of the aspiration funds and the absence of reporting to the local government by related parties who are given responsibility. 3). The responsibility for the aspiration fund is the project implementer to the government because before the contractor's funds are replaced there must be a team that assesses the feasibility of the development, if the project implementer cannot account for the utilization of this aspiration fund, the smallest consequence may be that the project implementer will not get replacement funds and will not be given Another project for the next and greatest consequence is problematic in the legal shutter.